2009
DOI: 10.3354/meps08143
|View full text |Cite
|
Sign up to set email alerts
|

Lipid biomarkers reveal geographical differences in food supply to the cold-water coral Lophelia pertusa (Scleractinia)

Abstract: Despite its importance as an ecological engineer, little is known about the feeding ecology of the widespread reef framework-forming cold-water coral Lophelia pertusa. This is the first study to compare lipid signatures of L. pertusa from different areas in the North Atlantic using samples from 2 sites in the eastern Atlantic and 2 seamounts in the western Atlantic. Lipid samples were collected in February, May, July and November from the Mingulay reef complex off western Scotland, but no clear seasonal patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
94
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 69 publications
4
94
1
Order By: Relevance
“…The lipids present were dominated by wax esters, probably reflecting a diet rich in herbivorous calanoid copepods that, at high latitudes, lay down their lipid reserves as wax esters. Mirroring the findings of Kiriakoulakis et al (2005), Dodds et al (2009) also reported monosaturated fatty acids C 20:1 and C 22:1 , both derived from calanoid copepods, and a lower proportion of phytoplankton-derived polyunsaturated fatty acids. On balance, these lipid biomarkers indicate that L. pertusa at Mingulay feeds predominantly on herbivorous calanoid copepods, but at deeper offshore bank and seamount settings carnivorous or omnivo- Relationship between mean rate of oxygen consumption (± SE) of L. pertusa and oxygen partial pressure (pO 2 ) at 3 different temperatures (6.5, 9 and 11°C).…”
Section: Coral Ecophysiologymentioning
confidence: 62%
“…The lipids present were dominated by wax esters, probably reflecting a diet rich in herbivorous calanoid copepods that, at high latitudes, lay down their lipid reserves as wax esters. Mirroring the findings of Kiriakoulakis et al (2005), Dodds et al (2009) also reported monosaturated fatty acids C 20:1 and C 22:1 , both derived from calanoid copepods, and a lower proportion of phytoplankton-derived polyunsaturated fatty acids. On balance, these lipid biomarkers indicate that L. pertusa at Mingulay feeds predominantly on herbivorous calanoid copepods, but at deeper offshore bank and seamount settings carnivorous or omnivo- Relationship between mean rate of oxygen consumption (± SE) of L. pertusa and oxygen partial pressure (pO 2 ) at 3 different temperatures (6.5, 9 and 11°C).…”
Section: Coral Ecophysiologymentioning
confidence: 62%
“…Recent in situ investigations using stable isotope and fatty acid analyses point to a close coupling of L. pertusa with pelagic resources such as zooplankton and phytodetritus (Spiro et al, 2000;Duineveld et al, 2004;Kiriakoulakis et al, 2005). While tidal pumping (Davies et al, 2009) and internal waves (Frederiksen et al, 1992;Duineveld et al, 2004) deliver a diverse range of particles to the coral, ranging from fresh to resuspended material, the vertical migration (daily or seasonal) of zooplankton can also contribute to the linkage between surface-water production and CWC nutrition (Hind et al, 2000;Valle-Levinson et al, 2004;Dodds et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of natural stable isotope signatures in tissues allow insight into the coral nutrition as described above (Duineveld et al, 2004;Kiriakoulakis et al, 2005;Dodds et al, 2009;Roberts et al, 2009b;van Oevelen et al, 2009), but to enhance the resolution of bulk tissue isotope data, fatty acids are often used as a biomarkers in these studies…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…zooplankton) efficiently captured from surrounding waters (Purser et al, 2010;Tsounis et al, 2010). There is consensus based on studies employing lipid biomarkers, stable isotopes and in situ video surveys that zooplankton represents a potential dietary component for the dominant cosmopolitan CWC species (Kiriakoulakis et al, 2005;Dodds et al, 2009;van Oevelen et al, 2009;Purser et al, 2010;Tsounis et al, 2010). However, none of these studies have investigated physiological processes of live CWC specimens with respect to the availability of zooplankton food sources, and thus there is no direct evidence for the trophic significance of zooplankton feeding by CWC available to date.…”
Section: Introductionmentioning
confidence: 99%